A new C21 steroidal compound from the whole herb of Pachysandra terminalis Sieb. et Zucc. (August 2020) - Zhang, Yangyang; Li, Yuze; Xu, Yue; Fan, Hao; Huang, Wenli; Zhang, Huawei; Wang, Wei; Song, Xiaomei
Abstract: A new C21 steroidal compound (1 ), along with 12 known compounds (2 –13 ) were isolated from the whole herb of Pachysandra terminalis Sieb. et Zucc. Their structures were determined by extensive analysis using various spectroscopic techniques. Notably, compound 6 was reported for the first time from P. terminalis, and compounds 3 –5, 7 and 9 were isolated from the family Buxaceae for the first time. Graphical abstract: Image 1 Highlights: Thirteen compounds were isolated from the whole herb of Pachysandra terminalis, one of which was a new compound. 6 was reported for the first time from P. terminalis, and 3-5, 7 and 9 were identified for the first time in Buxaceae . Our findings have showed the chemotaxonomic significance of P. terminalis.